2020
DOI: 10.1111/risa.13604
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Risk and Impact Screening of Chemicals in Consumer Products

Abstract: The ubiquitous presence of more than 80,000 chemicals in thousands of consumer products used on a daily basis stresses the need for screening a broader set of chemicals than the traditional well‐studied suspect chemicals. This high‐throughput screening combines stochastic chemical‐product usage with mass balance‐based exposure models and toxicity data to prioritize risks associated with household products. We first characterize product usage using the stochastic SHEDS‐HT model and chemical content in common ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…When translating the functional unit into daily use, we would arrive at impacts per individual usage per person. With that, our framework can also be applied in chemical exposure assessment and risk prioritization frameworks (Fantke and Illner 2019;Fantke et al 2020a;Jolliet et al 2021).…”
Section: Case Study On Rice Production and Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…When translating the functional unit into daily use, we would arrive at impacts per individual usage per person. With that, our framework can also be applied in chemical exposure assessment and risk prioritization frameworks (Fantke and Illner 2019;Fantke et al 2020a;Jolliet et al 2021).…”
Section: Case Study On Rice Production and Consumptionmentioning
confidence: 99%
“…Such improvements are mainly related to increasing the spatiotemporal and population-level resolution of impact estimates and extending the coverage and quality of substance, exposure, and dose-response information (Fantke et al 2018a,b;Kirchhübel & Fantke 2019;Crenna et al 2020;Gentil et al 2020;Holmquist et al 2020). Furthermore, a series of recent studies has demonstrated that environmentally mediated exposure from chemical emissions is less important for overall exposure than consumer exposure to chemical constituents in products (Shin et al 2015;Ernstoff et al 2016;Csiszar et al 2017;Ring et al 2019;Fantke et al 2020b;Jolliet et al 2021). Hence, including pathways related to chemicals in consumer products into toxicity characterization frameworks is crucial for considering all relevant pathways.…”
Section: Introductionmentioning
confidence: 99%
“…and a more sophisticated approach to regulatory decision making in the face of this uncertainty. These issues are common to many of the papers and several (e.g., Chiu & Paoli, 2021; Jolliet et al., 2021; Rheinberger, 2021; von Stackelberg & Williams, 2021) point the way to future progress.…”
Section: Discussionmentioning
confidence: 95%
“…The three papers in the fifth session applied risk assessment and economic valuation to health risks. One estimated the costs of developing a complex therapeutic medical device (Sertkaya, Jessup, & DeVries, 2019), a second considered chemicals in consumer products (Jolliet, Huang, Hou, & Fantke, 2021), and a third estimated the benefits of decreasing childhood lead exposure (Zhou & Grosse, 2019). The sixth session returned to air pollution, focusing on interventions to reduce exposure.…”
Section: Workhop Themesmentioning
confidence: 99%
See 1 more Smart Citation